A literature review of lesson study in initial teacher education: Perspectives about learning and observation. Issue 1 (2nd January 2018) - Larssen, Deborah Lynn Sorton; Cajkler, Wasyl; Mosvold, Reidar; Bjuland, Raymond; Helgevold, Nina; Fauskanger, Janne; Wood, Phil; Baldry, Fay; Jakobsen, Arne; Bugge, Hans Erik; Næsheim-Bjørkvik, Gro; Norton, Julie
Abstract : Purpose: The purpose of this paper is to conduct a structured review of literature on lesson study (LS) in initial teacher education (ITE). The focus was on how learning and observation were discussed in studies of LS in ITE. Design/methodology/approach: Each national team (in Norway and Britain) undertook independent searches of published peer-reviewed articles. The resulting articles were then combined, screened and collaboratively reviewed, the focus being on two areas of enquiry: how learning is represented and discussed; and the extent to which observation is described and used to capture evidence of learning. Findings: The literature review indicated that there was no universally held understanding of, or explanation for, the process of observation, how it should be conducted, and who or what should be the principal focus of attention. There was also a lack of clarity in the definition of learning and the use of learning theory to support these observations. Research limitations/implications: This study was limited to a review of a selection of peer-reviewed journal articles, published in English. It arrives at some tentative conclusions, but its scope could have been broadened to include more articles and other types of published material, e.g. theses and book chapters. Practical implications: Research that investigates the use of LS in ITE needs to be more explicit about how learning is defined and observed. Furthermore, LS research papers need to assure greater clarity and transparency about how observations are conducted in their studies. Originality/value: This literature review suggests that discussion of both learning and observation in ITE LS research papers should be strengthened. The review highlights three principal challenges that ITE LS researchers should consider: how to prepare student-teachers to observe (professional noticing being a promising option), the wide variation in the focus of classroom observation in ITE lesson studies, and discussion of what is understood by learning needs to stand at the heart of preparation for lesson studies in ITE.